Relasi Pengetahuan dan Ruang Arsitektural : Telaah Jaringan-Aktor Kampung Sepatu Cibaduyut dan Jenama Sepatu Ekspor di Bandung - Andayani, Firda Rasyidian; Ekomadyo, Agus Suharjono (Fakultas Seni Rupa dan Desain ITB, 2024)
Kampung sepatu Cibaduyut in Bandung is known as a Cibaduyut shoe village and as a residential area with dominant shoe industry activities. Knowledge of shoemaking was preserved from generation to generation in this village. Kampung Cibaduyut had business relationships with branded shoe entrepreneurs, including export shoe brands in Bandung such as Tegep Boots and Exodos57. Through these relationships, the basic knowledge network of kampung sepatu Cibaduyut could develop to reach the global market. This study aims to explore the architectural spaces (artifacts) and human actors who play an important role in bringing local knowledge to Cibaduyut so that it can be used by foreign consumers using the Actor-Network Theory (ANT) method. The results of this study showed that production spaces in the form of workshops and home industries in kampung sepatu Cibaduyut were places where knowledge was transferred through local brand export shoes to foreign countries.